Pendampingan Pembelajaran Al-Qur’an melalui Metode UMMI bagi Jamaah Ibu-Ibu di Masjid Baiturrahman Rungkut Surabaya - Imam Subeki Firmanto; Nelud Darajaatul Aliyah (Journal of Research and Community Service, 2024)
This program was carried out to improve the quality of Qur’an recitation among women congregants at Baiturrahman Mosque, Rungkut, Surabaya. The main issue addressed was the low ability to read the Qur’an with tartil and the lack of an effective, adult-friendly learning method. The activity has been implemented since January 1, 2023-2025, involving 45 participants (aged 25-50 years) and three certified UMMI instructors, with weekly sessions held every Saturday from 06:30 to 08:00 a.m. The implementation adopted a participatory mentoring approach based on the UMMI method, consisting of needs assessment, grouping after tashih evaluation, classical and individual learning sessions, and continuous monitoring. Program evaluation was conducted through tashih tests (recitation accuracy), instructor observation, attendance monitoring, and participant satisfaction questionnaires. The results indicate notable improvements in reading fluency, pronunciation of Arabic letters, and basic understanding of tajwid, as recorded in tashih assessments and instructor reports. Social impacts included increased participant engagement, higher self-confidence, and strengthened social bonds (ukhuwah islamiyah) among the women congregants. For sustainability, the program is recommended to continue through facilitator training for mosque administrators, periodic evaluation, and extended collaboration with the UMMI Foundation